Pengaruh Financial Distress, Umur Perusahaan, dan Good Corporate Governance pada Kecepatan Publikasi Laporan Keuangan Tahunan - Paulalengan, Arl Jonathan; Dwi Ratnadi, Ni Made (E-Jurnal Akuntansi; Vol 27 No 3 (2019)DO - 10.24843/EJA.2019.v27.i03.p14, 2019)
The purpose of this study examines the effect of financial distress, company age, and good corporate governance on the speed of publication of annual financial statements. This research was focused in the food and beverage companies listed on Indonesia Stock Exchange (IDX). Samples are determined by non-probability sampling, purposive sampling technique. Sample criteria, the company reports its annual financial statements in a row from 2014 to 2017. The samples were 12 companies with four years of observation. Methods of collecting data with non-participant observation, accessing annual financial reports. The data analysis technique is multiple linear regression. Based on the results, found that financial distress had a negative effect on the speed of publication of annual financial statements. The age of the company does not affect the speed of publication of annual financial statements. Good corporate governance has a positive effect on the speed of publication of annual financial statements. Keywords:  Publication, distress, good corporate governance, age